(untitled) (Journal of Shaheed Suhrawardy Medical College, 2013)
Background: Lateral malleolus is the key structure for anatomic reduction of the displaced bi-malleolar fracture and that restored the integrity of stability of ankle. Therefore, accurate reduction and fixation is needed for proper functioning of the joint. Objectives: The purpose of the present study was to find out the better method of fixation for the unstable lateral malleolar fracture between tension band wiring and semitubular plating. Methodology: This was a prospective study carried out the National Institute of Traumatology and Orthopaedic Rehabilitation (NITOR) Dhaka during the period of July 2000 and June 2002. All the relevant data were collected for each individual patient on a predesigned data sheet and analyzed. A p value of <0.05 was taken as minimum level of significance. Result: Twenty patients were available till the final follow up. Tension band wiring was done for ten patients and semitubular plating for the rest ten patients. All fractures were united in 12 weeks in plating group and in tension band wiring group union occurred as early as 10 weeks. Radiological evaluation continued at 18th and 24th week showed no signs of osteoarthritis or any deformity. Conclusion: Displaced lateral malleolar fractures demands operative treatment and tension band wiring using 2 k-wires provide stronger fixation and fracture united early. DOI: http://dx.doi.org/10.3329/jssmc.v5i2.20760 J Shaheed Suhrawardy Med Coll, 2013;5(2):81-83